A New Perspective of Inferring from the output of Linear Cryptanalysis Attack - Bhowmik, Dipanjan; Datta, Avijit; Sinha, Sharad (International Journal of Computer Sciences and Engineering, 2025)
In this paper the results obtained from Linear Cryptanalysis attack developed by Matsui has been analyzed in a different perspective and inferences were drawn accordingly[2]. Here, a simple toy cipher has been put to Linear Cryptanalysis attack in order to understand the attack from a different perspective. The results thus obtained may become a guide towards designing block ciphers that can withstand Linear Cryptanalysis attacks.